Radiolabeled theranostics: magnetic and gold nanoparticles - Saeideh Same; Ayuob Aghanejad; Sattar Akbari Nakhjavani; Jaleh Barar; Yadollah Omidi (BioImpacts, 2016)
Introduction: Growing advances in nanotechnology have facilitated the applications of newly emerged nanomaterials in the field of biomedical/pharmaceutical sciences. Following this trend, the multifunctional nanoparticles (NPs) play a significant role in development of advanced drug delivery systems (DDSs) such as diapeutics/theranostics used for simultaneous diagnosis and therapy. Multifunctional radiolabeled NPs with capability of detecting, visualizing and destroying diseased cells with least side effects have been considered as an emerging filed in presentation of the best choice in solving the therapeutic problems. Functionalized magnetic and gold NPs (MNPs and GNPs, respectively) have produced the potential of nanoparticles as sensitive multifunctional probes for molecular imaging, photothermal therapy and drug delivery and targeting. Methods: In this study, we review the most recent works on the improvement of various techniques for development of radiolabeled magnetic and gold nanoprobes, and discuss the methods for targeted imaging and therapies. Results: The receptor-specific radiopharmaceuticals have been developed to localized radiotherapy in disease sites. Application of advanced multimodal imaging methods and related modality imaging agents labeled with various radioisotopes (e.g., 125I, 111In, 64Cu, 68Ga, 99mTc) and MNPs/GNPs have significant effects on treatment and prognosis of cancer therapy. In addition, the surface modification with biocompatible polymer such as polyethylene glycol (PEG) have resulted in development of stealth NPs that can evade the opsonization and immune clearance. These long-circulating agents can be decorated with homing agents as well as radioisotopes for targeted imaging and therapy purposes. Conclusion: The modified MNPs or GNPs have wide applications in concurrent diagnosis and therapy of various malignancies. Once armed with radioisotopes, these nanosystems (NSs) can be exploited for combined multimodality imaging with photothermal/photodynamic therapy while delivering the loaded drugs or genes to the targeted cells/tissues. These NSs will be a game changer in combating various cancers.